Micro-arc oxidation method for tantalum metal surface
By using sodium chloride electrolyte on the surface of tantalum metal for microarc oxidation, a porous Ta2O5 oxide film was generated, which solved the problems of impure, high cost and incompatibility of the oxide film in the prior art, and realized the tantalum metal Effective application in orthopedic materials.
Patent Information
- Application Number
- CN202411880814.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing tantalum metal microarc oxidation technology, the selection of electrolyte results in impure, high cost and inconsistent with biocompatibility requirements, especially in orthopedic implant materials.
Sodium chloride is used as the electrolyte and microarc oxidation is performed on the surface of the tantalum metal to form a porous Ta2O5 oxide film. This method controls the current density, duty cycle and frequency, and adjusts the electrolyte concentration to prepare a porous oxide film with controllable morphology.
It realizes rapid generation of porous Ta2O5 coatings with excellent corrosion resistance and biocompatibility, improves the specific surface area and smoothness of tantalum metal, promotes the proliferation and adhesion of osteoblasts, and solves the tantalum metal in orthopedic materials. Application disadvantages.
Smart Images

Figure BDA0005198157560000101 
Figure HDA0005198157570000011 
Figure HDA0005198157570000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry and relates to a micro-arc oxidation method for a tantalum metal surface in a sodium chloride electrolyte. Background Art
[0002] Tantalum is a metal with excellent properties. It has a high melting point (up to 2995°C), good chemical stability, strong ductility, toughness and high density (16.68g / cm 3 ) has been continuously developed in various fields, especially in medical treatment, including Ta wire for surgical incision suture, Ta stent implant for vascular stenosis, Ta nail in early femoral osteonecrosis, Ta rod and joint for supporting bone defects. These biological applications show that tantalum metal can be used as a permanent biomedical material implant with good biocompatibility. Despite its high toughness and ductility, its long-term corrosion in body fluids and low specific surface area are not suitable for the reproduction and survival of osteoblasts, which seriously affects its application in bone implant materials. Therefore, forming a porous oxide film on the surface of tantalum will greatly improve its biocompatibility.
[0003] Micro arc oxidation (MAO), also known as plasma electrolytic oxidation (PEO), is an electrochemical technology that uses plasma to assist the oxidation of various valve metals (such as Mg, Al, Ti, Zr, Nb, Hf and Ta). Micro arc oxidation technology can prepare a protective inorganic coating on the surface of the metal substrate, thereby improving its wear resistance and corrosion resistance. At present, the electrolytes selected for micro arc oxidation of tantalum metal are mostly phosphates, silicates, aluminates and other electrolytes.
[0004] For example, the prior art CN114952181A relates to a method for preparing a highly corrosion-resistant tantalum and tantalum-tungsten alloy cylindrical part, which belongs to the field of preparation and processing technology of rare metals and can be used for the preparation and processing of pure tantalum and Ta-2.5W alloy cylindrical parts with a diameter of 150mm to 400mm. The process steps adopted are: deep drawing → cleaning → vacuum heat treatment → machining → cleaning → micro-arc oxidation → cleaning → polishing. The composition of the electrolyte solution is: 2 to 3 g / L of sodium hydroxide, 3 to 4 g / L of sodium aluminate, and 3 to 4 g / L of sodium phosphate.
[0005] Prior art CN114507893B provides an electrolyte and preparation method for a high-hardness and wear-resistant micro-arc oxidation coating on a tantalum alloy surface, which is used to effectively improve the hardness and wear resistance of the micro-arc oxidation coating. The electrolyte for the high-hardness and wear-resistant micro-arc oxidation coating on the tantalum alloy surface includes: a main film-forming agent, a pH regulator and an additive. The main film-forming agent is Na 3 PO 4The pH regulator is NaOH; the additives include: a film thickening agent, an arc suppressant and a hard phase decomposer, the hard phase decomposer is a soluble aluminum salt that can be decomposed into hard phase particles, and the aluminum salt is NaAlO 2 , KAlO 2 The film thickening agent is NaF, KF, Na 2 S, wherein the arc inhibitor is one or more of disodium ethylenediaminetetraacetate, hexamethylenetetraammonium, and glycerol.
[0006] During the micro-arc oxidation process, the anions in the electrolyte combine with the metal cations to form a ceramic layer on the surface of the metal substrate. Phosphates, silicates, aluminates and other electrolytes have the function of promoting the passivation of the metal surface and thus smoothly establishing spark discharge. Therefore, the above electrolytes are used in the prior art. However, the above electrolytes generally introduce impurities and cannot generate a pure oxide film; secondly, compared with NaCl, the preparation cost of the above electrolytes is high and it is not easy to reduce the cost; in addition, these electrolytes contain Al 3+ Ions (aluminum salt electrolyte), and aluminum has been shown to be one of the factors leading to Alzheimer's disease and other neurological diseases; finally, most of the membranes using this type of electrolyte are dense and do not meet the biocompatibility requirements. Currently, the micropore size of orthopedic medical materials is in the range of 0.1-5μm. The micropore size of the membrane layer prepared with this type of electrolyte does not meet the requirements.
[0007] As an inorganic salt that regulates the osmotic pressure balance in the human body, NaCl is not only low-cost, but also green and healthy. However, since chloride ions are corrosive particles that destroy the stability of metal passivation films, conventional metals cannot establish spark discharge in NaCl electrolytes. After applying the anode voltage, the metal will undergo severe dissolution corrosion. Therefore, to date, NaCl has only been used as a corrosion reagent to test corrosion resistance in micro-arc oxidation, and no one has ever used it as an electrolyte. Summary of the invention
[0008] The purpose of the present invention is to provide a method for micro-arc oxidation of tantalum metal surface in sodium chloride electrolyte.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A micro-arc oxidation method for a tantalum metal surface, using tantalum metal as an anode, performing micro-arc oxidation treatment, and obtaining Ta on the surface 2 O 5 Coating; The electrolyte used for micro-arc oxidation treatment is sodium chloride.
[0011] The present invention provides a micro-arc oxidation method for rapidly generating a biocompatible coating containing a large amount of tantalum oxide on the surface of tantalum metal. The pretreated tantalum metal is placed in an electrolyte for micro-arc oxidation to generate a biocompatible coating containing a large amount of porous tantalum. 2 O 5 Micro-arc oxidation coating.
[0012] In one preferred embodiment, the micro-arc oxidation method of the tantalum metal surface comprises the following steps:
[0013] S1. Grind, clean and dry the surface of the tantalum metal sample in sequence for later use;
[0014] S2, using the treated tantalum metal sample as the anode and the inactive metal as the cathode, micro-arc oxidation treatment was performed for 5s-20min to obtain Ta on the surface 2 O 5 coating;
[0015] During micro-arc oxidation treatment, the anode current density is controlled to be 1-50A / dm 2 , cathode current density is 0-50A / dm 2 , positive and negative duty cycle is 5%-80%, frequency is 10-50000Hz;
[0016] The electrolyte used in micro-arc oxidation treatment is sodium chloride.
[0017] In one preferred embodiment, the inactive metal is one of stainless steel, carbon steel, nickel metal or platinum metal.
[0018] In one preferred embodiment, the micro-arc oxidation treatment time is 10s-20min.
[0019] If the time is too short, the pores will be small; if the time is too long, the film adhesion will deteriorate.
[0020] In one of the preferred embodiments, the electrolyte temperature is controlled at 10-50°C during the micro-arc oxidation reaction.
[0021] In one preferred embodiment, the positive and negative duty ratios are 5%-20%.
[0022] In one preferred embodiment, the frequency is 10-1000 Hz.
[0023] In one preferred embodiment, the Ta 2 O 5 The thickness of the coating is 10-60 μm.
[0024] In one preferred embodiment, the Ta 2 O 5 The pore size of the coating is 1-5 μm.
[0025] The micropores provide osteoblasts with a larger specific surface area, which is beneficial to the initial attachment of cells. Osteoblasts can better adhere to the surface of the material and the areas around the micropores, and then carry out subsequent growth, differentiation and other processes.
[0026] In one preferred embodiment, the concentration of the electrolyte is 0.1-6.1 mol / L.
[0027] If the electrolyte concentration is too low, the resulting oxide film will not be dense; if the electrolyte concentration is too high, the sodium chloride will not be completely dissolved, which will have an adverse effect on the electrolysis process.
[0028] In one preferred embodiment, the concentration of the electrolyte is 0.1-2 mol / L.
[0029] In one preferred embodiment, the concentration of the electrolyte is 0.1-1.5 mol / L; preferably, the concentration of the electrolyte is 1.0 mol / L.
[0030] In one of the preferred embodiments, the purity of tantalum in the tantalum metal sample is not less than 99.90 wt %.
[0031] In one preferred embodiment, the tantalum metal sample is (0.2-0.05) mm×(80-120) mm×(80-120) mm.
[0032] The tantalum metal sample is (0.2-0.05) mm thick × (80-120) mm long × (80-120) mm wide.
[0033] In one preferred embodiment, the tantalum metal sample is polished using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence.
[0034] In one preferred embodiment, leave 0.5-1.5cm of the polished area. 2 Bare, the other end exposed 0.3-0.7cm 2 Used to connect the wires, wrap the rest with acid and alkali resistant tape, and apply silicone rubber on the tape surface.
[0035] In one preferred embodiment, the polished tantalum metal sample is rinsed with deionized water and alcohol, then subjected to ultrasound to remove oil stains, and finally taken out and dried.
[0036] In one preferred embodiment, before the micro-arc oxidation starts, the micro-arc oxidation device is first cleaned with distilled water and alcohol. The micro-arc oxidation device includes a micro-arc oxidation cathode, a reaction device, a jacketed beaker, and a stirring rod.
[0037] Based on the same inventive concept, the present invention also claims protection for an electrolyte for micro-arc oxidation of tantalum metal surface, wherein the electrolyte is sodium chloride.
[0038] In one preferred embodiment, the concentration of the electrolyte is 0.1-6.1 mol / L.
[0039] Based on the same inventive concept, the present invention also claims to protect the use of sodium chloride in micro-arc oxidation of tantalum metal surfaces.
[0040] In one preferred embodiment, the concentration of the electrolyte is 0.1-6.1 mol / L.
[0041] The present invention will be further explained and described below:
[0042] The present invention aims to provide a tantalum metal matrix Ta suitable for osteoblast growth 2 O 5 The micro-arc oxidation method of the porous coating can effectively solve the problems of tantalum metal in joint repair and metal implantation, making it widely used in orthopedic implant materials.
[0043] The present invention forms a film of tantalum metal in a sodium chloride electrolyte with a certain concentration, breaking the limitation of using phosphate and silicate electrolytes to prepare ceramic films in the previous micro-arc oxidation process.
[0044] The present invention obtains Ta with excellent corrosion resistance through micro-arc oxidation 2 O 5 Oxide film, this method has simple preparation conditions, fast film formation speed, and porous Ta film 2 O 5 Passivation film, Ta 2 O 5 The passivation film has a porous structure relative to the tantalum metal substrate. 2 O 5 It has strong corrosion resistance and can protect the tantalum metal substrate from corrosion. At the same time, the porous coating obtained by micro-arc oxidation improves the specific surface area and smoothness of the tantalum metal substrate. The porous coating promotes the proliferation and adhesion of osteoblasts, solves the current disadvantages of tantalum metal orthopedic materials, and improves the recovery speed of patients. The present invention can prepare a porous Ta with controllable morphology by using sodium chloride electrolyte. 2 O 5 The oxide film structure, for example, generates a crater morphology under higher concentration conditions (0.5-1.5 mol / L), and generates a worm-like or coral-like structure under lower concentration conditions (0.1-0.15 mol / L). The morphology can be flexibly controlled according to actual needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1This is a SEM morphology image of the coating prepared in Example 1 of the present invention;
[0046] Figure 2 This is a SEM morphology image of the coating prepared in Example 2 of the present invention;
[0047] Figure 3 This is a SEM morphology image of the coating prepared in Comparative Example 1 of the present invention;
[0048] Figure 4 This is a SEM morphology image of the coating prepared in Example 3 of the present invention;
[0049] Figure 5 This is a SEM morphology image of the coating prepared in Comparative Example 2 of the present invention;
[0050] Figure 6 This is a SEM morphology image of the coating prepared in Comparative Example 3 of the present invention;
[0051] Figure 7 XRD diagrams of Example 1, Example 2 and tantalum metal substrate film layer samples of the present invention;
[0052] Figure 8 Polarization curves of Example 1, Example 2, Comparative Example 1 and a tantalum metal substrate film layer of the present invention;
[0053] Fig. 9 Polarization curve diagrams of the tantalum metal substrate film layer of Embodiment 4 and Embodiment 5 of the present invention;
[0054] Fig.10 This is a SEM cross-sectional view of the film layer prepared in Example 2 of the present invention;
[0055] Fig.11 This is a SEM cross-sectional view of the film layer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0057] In this experiment, a scanning electron microscope (Nova Nano SEM230) produced by FEI Company of the United States was used to perform microscopic surface and cross-sectional morphology analysis on the film layer.
[0058] In this experiment, X-ray diffractometer (XRD, Rigaku D / max 2500) was used to characterize the phase composition and crystal structure of the PEO film layer.
[0059] Example 1
[0060] A micro-arc oxidation method for preparing a biocompatible coating of porous crystalline tantalum oxide in a NaCl electrolyte comprises the following steps:
[0061] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0062] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0063] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0064] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty ratios were set to 20%, the frequency was maintained at 1000 Hz, the electrolyte consisted of 1 mol / L NaCl, the micro-arc oxidation time was 10 min, the anode sample was taken out, and it was washed and dried in turn with deionized water and anhydrous ethanol, and then air-dried to obtain a porous crystalline tantalum oxide prepared in NaCl electrolyte.
[0065] Example 2
[0066] A micro-arc oxidation method for preparing a biocompatible coating of porous crystalline tantalum oxide in a NaCl electrolyte comprises the following steps:
[0067] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0068] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0069] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0070] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty ratios were set to 20%, the frequency was maintained at 1000 Hz, the electrolyte consisted of 0.1 mol / L NaCl, the micro-arc oxidation time was 10 min, the anode sample was taken out, and it was washed and dried in turn with deionized water and anhydrous ethanol, and then air-dried to obtain a porous crystalline tantalum oxide prepared in NaCl electrolyte.
[0071] Example 3
[0072] A micro-arc oxidation method for preparing a biocompatible coating of porous crystalline tantalum oxide in a NaCl electrolyte comprises the following steps:
[0073] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0074] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0075] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0076] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 30A / dm 2 The positive and negative duty ratios were set to 20%, the frequency was maintained at 1000 Hz, the electrolyte consisted of 1 mol / L NaCl, the micro-arc oxidation time was 10 min, the anode sample was taken out, and it was washed and dried in turn with deionized water and anhydrous ethanol, and then air-dried to obtain a porous crystalline tantalum oxide prepared in NaCl electrolyte. Its morphology is as follows Figure 4 As shown, it is a porous crystalline structure.
[0077] Example 4
[0078] A micro-arc oxidation method for preparing a biocompatible coating of porous crystalline tantalum oxide in a NaCl electrolyte comprises the following steps:
[0079] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0080] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0081] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0082] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty ratios were set to 20%, the frequency was maintained at 1000 Hz, the electrolyte consisted of 0.1 mol / L NaCl, the micro-arc oxidation time was 30 s, the anode sample was taken out, and it was washed and dried in turn with deionized water and anhydrous ethanol, and then air-dried to obtain a porous crystalline tantalum oxide prepared in NaCl electrolyte.
[0083] Example 5
[0084] A micro-arc oxidation method for preparing a biocompatible coating of porous crystalline tantalum oxide in a NaCl electrolyte comprises the following steps:
[0085] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0086] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0087] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0088] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty ratios were set to 20%, the frequency was maintained at 1000 Hz, the electrolyte consisted of 1 mol / L NaCl, the micro-arc oxidation time was 5 min, the anode sample was taken out, and it was washed and dried in turn with deionized water and anhydrous ethanol, and then air-dried to obtain a porous crystalline tantalum oxide prepared in NaCl electrolyte.
[0089] Comparative Example 1
[0090] A micro-arc oxidation method for preparing a biocompatible coating of tantalum oxide in a NaCl electrolyte comprises the following steps:
[0091] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0092] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0093] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0094] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty ratios are set to 20%, the frequency is maintained at 1000Hz, the electrolyte is composed of 0.01mol / L NaCl, the micro-arc oxidation time is 10min, the anode sample is taken out, and it is washed and dried in turn with deionized water and anhydrous ethanol, and then dried in the air to obtain a tantalum oxide prepared in NaCl electrolyte. Its morphology is as follows Figure 3 As shown, it is a dense structure that cannot meet the biological requirements.
[0095] Comparative Example 2
[0096] A micro-arc oxidation method for preparing a coating in a calcium hydrogen phosphate electrolyte comprises the following steps:
[0097] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0098] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2 After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0099] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0100] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty cycles were set to 20%, the frequency was maintained at 1000 Hz, and the electrolyte consisted of 0.05 mol / L Ca(H 2 PO 4 ) 2 ·H 2 O composition, micro-arc oxidation time 10min, take out the anode sample, wash it with deionized water and anhydrous ethanol in turn, and then dry it to obtain a dense film layer, such as Figure 5 As shown. The film layer contains Ta 2 O 5 、CaTa 2 O 6、 CaP 2 O 7 And other ingredients.
[0101] Comparative Example 3
[0102] A micro-arc oxidation method for preparing a coating in a calcium hydrogen phosphate electrolyte comprises the following steps:
[0103] (1) Cut the tantalum metal sheet (0.3*100*100mm) into thin sheets (0.3*10*100mm) using a wire cutting machine;
[0104] (2) Select one end of the slice obtained by the wire cutting machine in step (1), and grind it into a 1 cm thick piece using 150#, 600#, 1000#, 2000#, and 3000# SiC sandpaper in sequence. 2After polishing, rinse the (10*10mm) area with distilled water for 1-2 minutes, then put it into anhydrous ethanol for ultrasonic cleaning to remove the remaining stains, take it out and air dry it for later use;
[0105] (3) Leave 0.5 cm at the other end of the sample working area obtained in step (2). 2 The exposed end of the tantalum metal is sealed with acid-resistant polytetrafluoroethylene tape, and 704 silicone rubber is applied to the surface of the tantalum tape. It is placed to cool and air dry. After drying, it is cleaned and dried again with distilled water and alcohol. 0.5 cm is left on the other end of the sample. 2 Bare end and 1cm 2 Work area, attach the wire clamp to this exposed end.
[0106] (4) Using the tantalum metal sample obtained in step (3) as the anode and the stainless steel as the cathode, turn on the power supply and set the micro-arc oxidation parameters to a positive current of 40 A / dm 2 , negative current is set to 0A / dm 2 The positive and negative duty cycles were set to 20%, the frequency was maintained at 1000 Hz, and the electrolyte consisted of 0.1 mol / L Ca(H 2 PO 4 ) 2 ·H 2 O composition, micro-arc oxidation time 10min, take out the anode sample, wash it with deionized water and anhydrous ethanol in turn, and then dry it to obtain a dense film layer, such as Figure 6 shown.
[0107] Effect comparison experimental data:
[0108] According to the above method, a micro-arc oxidation film was obtained, and the film data of the micro-arc oxidation method with different concentrations of electrolyte was compared. Here, the data of the film layers of Examples 1-5 and Comparative Examples 1-3 were analyzed, and the test results are as follows:
[0109] Microstructure of the film
[0110] Figure 1 It can be observed from the SEM morphology that the film layer after micro-arc oxidation for 10 minutes at a concentration of 1 mol / L NaCl electrolyte (Example 1) presents a crater shape, the pore size is about 2-3 μm, and the pore size distribution is uniform. Figure 2 It was observed from the SEM morphology that when the NaCl electrolyte concentration was 0.1 mol / L, the film layer after 10 min of micro-arc oxidation (Example 2) appeared coral-like, with a pore size of about 1-5 μm, forming a loose and porous feature suitable for cell growth. Figure 3 When the concentration dropped to 0.01 mol / L (Comparative Example 1), the porous structure disappeared, and some relatively large independent nodules were distributed on the smooth surface. Figure 4 After applying cathode current for 10 min in micro-arc oxidation under 1 mol / L electrolyte conditions, the film layer (Example 3) still presents a crater shape, indicating that the application of cathode current does not affect the morphological characteristics of the sample. Figure 5 Then 0.01mol / L Ca(H 2 PO 4 ) 2 ·H 2 O electrolyte conditions (Comparative Example 2), it was observed that the film layer was dense, and there were some tiny breakdown holes on the surface of the film layer, which could not meet the biocompatibility requirements. Figure 6 It shows that Ca(H 2 PO 4 ) 2 ·H 2 As the concentration of O as the electrolyte changes, the morphology does not change significantly, indicating that the concentration change cannot regulate the microscopic morphology of the film layer. The film layer contains a large number of other components and is not a pure tantalum oxide film, which in turn affects the performance of the material.
[0111] Phase structure of the film
[0112] XRD pattern ( Figure 7 ) can be seen that the composition of the micro-arc oxidation coating is crystalline Ta 2 O 5 .
[0113] The corrosion performance of the films obtained in different concentrations of sodium chloride electrolyte is compared as follows: Figure 7-8 As shown in Table 1:
[0114] Table 1 Performance of the film after micro-arc oxidation with different electrolytes
[0115]
[0116] Figure 8 It is a polarization curve diagram of the film layer generated by micro-arc oxidation of tantalum metal and tantalum substrate for 10 minutes in 1 mol / L NaCl electrolyte (Example 1), 0.1 mol / L NaCl electrolyte (Example 2), 0.01 mol / L NaCl conditions (Comparative Example 1). Fig. 9 The polarization curves of the PEO film formed under different electrolyte concentrations and different time conditions (including Example 4 and Example 5) are shown in Figure 1. The corrosion resistance of the samples in 3.5wt.% NaCl solution was tested using an electrochemical workstation (CHI 660B). The test used a three-electrode system, with a platinum sheet and a saturated calomel electrode (SCE) as the auxiliary electrode and reference electrode, respectively. The surface area of the film was 1 cm2 and the surface area of the film was 1 cm2. 2The metal PEO film layer was used as the working electrode. The potentiodynamic polarization curves (PDP) of the samples were detected, and the polarization curves were used to obtain various data of corrosion resistance by Tafel extrapolation. The corrosion current density of all film layers was one order of magnitude lower than that of the tantalum matrix, indicating that the film layer exhibited good corrosion resistance. However, the microscopic morphology under 0.01 mol / L electrolyte conditions formed a dense structure, which did not meet the biocompatibility requirements.
[0117] Cross-sectional morphology of the film
[0118] Fig.10 The cross section of the coating of Example 2 is shown. Under this condition, the thickness of the coating is about 10 μm, and the film layer has no large defects or cracks. Fig.11 A cross section of the Example 1 coating is shown, showing a uniform and flat film layer up to a thickness of about 50 μm.
[0119] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for micro-arc oxidation of a tantalum metal surface, characterized in that: Tantalum metal is used as an anode and micro-arc oxidation treatment is carried out to obtain a Ta2O5 coating on the surface; the electrolyte used in the micro-arc oxidation treatment is sodium chloride.
2. The micro-arc oxidation method according to claim 1, characterized in that: The following steps are involved: S1. Grind, clean and dry the surface of the tantalum metal sample in sequence for later use; S2, using the treated tantalum metal sample as the anode and the inactive metal as the cathode, after micro-arc oxidation treatment for 5 s-20 min, a Ta2O5 coating is obtained on the surface; During micro-arc oxidation treatment, the anode current density is controlled to be 1-50A / dm 2 , cathode current density is 0-50A / dm 2 , positive and negative duty cycle is 5%-80%, frequency is 10-50000Hz; The electrolyte used in micro-arc oxidation treatment is sodium chloride.
3. The micro-arc oxidation method according to claim 2, characterized in that: The inactive metal is one of stainless steel, carbon steel, nickel metal or platinum metal.
4. The micro-arc oxidation method according to claim 2, characterized in that: The micro-arc oxidation treatment time is 10 s-20 min.
5. The micro-arc oxidation method according to claim 2, characterized in that: During the micro-arc oxidation reaction, the electrolyte temperature is controlled at 10-50 °C.
6. The micro-arc oxidation method according to claim 2, characterized in that: The thickness of the Ta2O5 coating is 10-60µm.
7. The micro-arc oxidation method according to claim 2, characterized in that: The concentration of the electrolyte is 0.1-6.1 mol / L.
8. The micro-arc oxidation method according to any one of claims 2 to 7, characterized in that: Before the micro-arc oxidation begins, the micro-arc oxidation device is first cleaned with distilled water and alcohol. The micro-arc oxidation device includes a micro-arc oxidation cathode, a reaction device, a jacketed beaker, and a stirring rod.
9. An electrolyte for micro-arc oxidation of tantalum metal surface, characterized in that: The electrolyte is sodium chloride; preferably, the concentration of the electrolyte is 0.1-6.1 mol / L.
10. Application of sodium chloride in micro-arc oxidation of tantalum metal surface, preferably, the concentration of the electrolyte is 0.1-6.1 mol / L.
Citation Information
Patent Citations
Electrolyte for High-Hardness and Wear-Resistant Micro-Arc Oxidation Coating on Tantalum Alloy Surface and its Preparation Method
CN114507893B
Preparation method of high-corrosion-resistance tantalum and tantalum-tungsten alloy cylindrical part
CN114952181A